Diagnostic Risk Management System (DRMS): An Assessment of Financial Risk - Mohamed Shuhidan, Shuhaida; Ahmad Nadzri, Farah Aida; Rafidi, Marhamah; Said, Jamaliah (Journal of Technology Management and Business, 2023)
Risk management is critical for any organisation to manage risk appropriately, as an undesirable risk event can have a huge negative impact on finances. Poor risk management leads to uncertain business performance or in the worst-case scenario, the collapse of the business. Sound risk management requires that the elements of risk in the business are considered before a decision is made. It is also important to know how the risk can be mitigated if it occurs, who is responsible for managing the risk, whether the likelihood and severity of the risk should be reduced or the risk should be avoided and transferred to others. This can help organisations to carry out the necessary assessments and analysis to understand the extent of their risk exposure and then plan mitigation measures. This paper highlights the importance of the Diagnostic Risk Management System (DRMS) as a lifesaver for organisations. Scholars, experts and practitioners generally agreed that DRMS reflects a company's image and subsequently reduces opportunities for fraud. DRMS is a user-friendly system that helps companies manage and view overall risk and find appropriate solutions to mitigate individual risks. DRMS focuses on the overall risk, especially on the risk assessment of financial reporting. DRMS is suitable for companies to create a competitive but healthy business environment that is free from destructive elements such as corruption, fraud and white-collar crime. This in turn ensures the creation of wealth for the business environment in Malaysia.